Psoriasis in children: clinical features and treatment modalities in Erbil city - Hussein Mahmood Mohammed; Mohammed Yousif Saeed (Advanced Medical Journal)
Background and objectives: Psoriasis is a common, chronic inflammatory disorder that affects the skin, nails, and joints. The purpose of this study was to identify clinical features and treatment modalities of psoriasis in children in Erbil city.